Ответ:
Объяснение:
C(x,y,z) =
C(x) =
-2 = (-4 + x)/2 --> x=0
C(y) =
4 = (6+y)/2 --> y=2
C(z) =
4 = (6+z)/2 --> z=2
Ответ: B(0; 2; 2)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
C(x,y,z) =![\frac{A(x) + B(x)}{2}; \frac{A(y) + B(y)}{2}; \frac{A(z) + B(z)}{2}; \frac{A(x) + B(x)}{2}; \frac{A(y) + B(y)}{2}; \frac{A(z) + B(z)}{2};](https://tex.z-dn.net/?f=%5Cfrac%7BA%28x%29%20%2B%20B%28x%29%7D%7B2%7D%3B%20%20%5Cfrac%7BA%28y%29%20%2B%20B%28y%29%7D%7B2%7D%3B%20%20%5Cfrac%7BA%28z%29%20%2B%20B%28z%29%7D%7B2%7D%3B)
C(x) =![\frac{A(x) + B(x)}{2}; \frac{A(x) + B(x)}{2};](https://tex.z-dn.net/?f=%5Cfrac%7BA%28x%29%20%2B%20B%28x%29%7D%7B2%7D%3B)
-2 = (-4 + x)/2 --> x=0
C(y) =![\frac{A(y) + B(y)}{2} \frac{A(y) + B(y)}{2}](https://tex.z-dn.net/?f=%5Cfrac%7BA%28y%29%20%2B%20B%28y%29%7D%7B2%7D)
4 = (6+y)/2 --> y=2
C(z) =![\frac{A(z) + B(z)}{2}; \frac{A(z) + B(z)}{2};](https://tex.z-dn.net/?f=%5Cfrac%7BA%28z%29%20%2B%20B%28z%29%7D%7B2%7D%3B)
4 = (6+z)/2 --> z=2
Ответ: B(0; 2; 2)